Representasi Budaya Jepang dalam Game Ensemble Stars - putu ditha ananda putri; Suartini Ni Nengah; Handayani Irvina Restu (Japanology: The Journal of Japanese Studies, 2025)
Video games, especially the roleplay game (RPG) genre, have evolved into an effective popular culture medium for representing and transmitting cultural values. This study aims to uncover and analyze the cultural representation of the Japanese New Year celebration (Shōgatsu) found in the roleplay game Ensemble Stars. Although Japanese culture is globally well-known, the deep understanding of the meaning and values behind it among the global community remains limited. Therefore, this research assesses the extent to which this game can serve as an accurate reference for cultural understanding. The research method used is content analysis through observation of in-game content. Data analysis was performed using the Edgar H. Schein cultural model, which divides cultural elements into three levels: artifacts (tangible culture), espoused values, and basic assumptions (intangible culture). Data were collected by identifying and recording storyline elements, decorations, and character interactions related to the Japanese New Year celebration. The results show that Ensemble Stars successfully and accurately represents the Japanese New Year culture, encompassing both tangible aspects (such as osechi and kadomatsu) and intangible aspects (such as the hatsumōde tradition and the value of togetherness). This representation functions as an effective cultural transmission medium, helping global players understand the values and meaning behind the traditions, and indirectly contributing to Japan's tourism promotion strategy.